Scale issues for geoheritage 3D mapping: The case of Lesvos Geopark, Greece - Ermioni Eirini Papadopoulou; Apostolos Papakonstantinou; Christos Vasilakos; Nikolaos Zouros; Georgios Tataris; Stavros Proestakis; Nikolaos Soulakellis (International Journal of Geoheritage and Parks, 2022)
A geopark can be composed of many individual geosites of various geographical scales, thus, categorization according to cartographic scale is crucial for their 3D mapping. The UNESCO Global Geopark of the island of Lesvos in the north-east Aegean, Greece, is a distinctive example of this type of geopark as it contains many unique geosites that vary in geographical scale. The geographical scale is interconnected with the cartographic scale in which the geosite is visualized. The desired cartographic scale is an essential user requirement within an unmanned aerial vehicle's (UAVs) 3D mapping project as the basis for the data acquisition strategy. This research investigates the scale issues in 3D mapping of geosites. Furthermore, it contributes to the incorporation of the geographic and cartographical scales in association with UAV flight parameters such as Ground Sample Distance (GSD), altitude, gimbal pitch, orientation, and front and side overlapping. A total of 132 geosites located in Lesvos Geopark are being studied to determine the flight parameters of three different UAVs and their camera characteristics. The methodology followed to collect very high-resolution images suitable for 3D mapping consists of five main stages: i) determining the geographical scale of each geosite, ii) defining the cartographic scale of all geosites, iii) calculation of the GSD based on cartographic scale, iv) calculation of UAV flight altitude and flight characteristics, and v) classification of geosites based on the flight characteristics for their 3D mapping. Five geographic (G1: < 0.1 ha, G2: 0.1–1 ha, G3: 1–10 ha, G4: 10–100 ha, G5: >100 ha) and five cartographic (C1: > 1:50, C2: 1:50–1:100, C3: 1:100–1:250, C4: 1:250–1:500, C5: < 1:500) categories were defined based on the geosites' size and extent. The combination of the two scales determines the most efficient flight characteristics and optimally acquires very high-resolution images required for the 3D mapping of the selected geosites. Finally, the categorization and characteristics of flights for data collection for high-resolution 3D mapping are collected and presented in a web application. The web application is addressed to the management board of Lesvos Geopark and supports the decision-making processes on mapping geosites using UAVs.